2010
DOI: 10.1002/jsfa.4047
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and phenolic content of wine vinegars produced by two different techniques

Abstract: Results of this study showed that different production methods affected the functional constituents of wine vinegars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
83
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 30 publications
8
83
0
4
Order By: Relevance
“…TEAC values of TGV and IGV samples were 11.82 mM and 10.44 mM, respectively. These findings were in concordance with previous studies [9,20]. Seeram et al [21] reported that TEAC and ORAC value of apple juice samples ranged between 2.5-6.2 µmol of TE/mL and 2.7-4.3 µmol/mL respectively.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…TEAC values of TGV and IGV samples were 11.82 mM and 10.44 mM, respectively. These findings were in concordance with previous studies [9,20]. Seeram et al [21] reported that TEAC and ORAC value of apple juice samples ranged between 2.5-6.2 µmol of TE/mL and 2.7-4.3 µmol/mL respectively.…”
Section: Resultssupporting
confidence: 92%
“…ORAC and TEAC levels of traditional wine vinegar were 10.50 µmol/mL TE and 13.50 mmol/L TEAC, while ORAC and TEAC levels of the industrial wine vinegar were 8.84 µmol/mL TE and 10.37 mmol/L TEAC [9]. In another study of traditional vinegar samples, the highest level of total phenolic and flavonoid compounds and the levels of anti-radical activity were obtained in grape vinegars [10].…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Density and Brix values were significantly decreased during alcohol fermentation due to the conversion of sugar to ethanol (P<0.05). Budak and Güzel-Seydim (2010) explained that total solids and Brix of samples significantly decreased after maceration due to pressing, resettling and racking during grape wine production. Brix of Cashew apple wine was found to be 2.0% (Mohanty et al, 2006).…”
Section: Composition Analysismentioning
confidence: 99%
“…Index of grapes, g Grapes structure index Grape composition index 95,31 17,98 7,32 Soluble dry substances, g/l 204,5 Total acidity of must, g/l H 2 SO 4 5,537 (Fig. 2).…”
Section: Uvological Indicesmentioning
confidence: 99%